2020
DOI: 10.3390/ijms21176068
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Antifouling Activity of Biosurfactants Producing Marine Bacteria Isolated from Gulf of California

Abstract: Biofouling causes major problems and economic losses to marine and shipping industries. In the search for new antifouling agents, marine bacteria with biosurfactants production capability can be an excellent option, due to the amphipathic surface-active characteristic that confers antimicrobial and antibiofilm activities. The aim of this study was to evaluate the antifouling activity of biosurfactants producing marine bacteria from the Gulf of California. The cell free culture supernatant (CFCS) of Bacillus ni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 90 publications
0
17
0
Order By: Relevance
“…Also, hexadecanoic acid, methyl ester and hexadecanoic acid, ethyl ester detected respectively in AE1 and AE2 have antibiofilm potentials and are associated with biosurfactant formation in an endophytic bacterium (Ashitha et al, 2020). Biosurfactant production is an important characteristic of Alcanivorax sp., which is an essential requirement for inhibiting the biofilm formation and biofouling growth (Qiao and Shao, 2010;Alemań-Vega et al, 2020;Mishra et al, 2020). The detection of fatty acids in the extracts along with strong antibiofilm activity in this study indicated the potential of sponge-associated Alcanivorax as a good source of antibiofilm compounds.…”
Section: Chemical Compounds From Alcanivorax Sp Extractsmentioning
confidence: 60%
“…Also, hexadecanoic acid, methyl ester and hexadecanoic acid, ethyl ester detected respectively in AE1 and AE2 have antibiofilm potentials and are associated with biosurfactant formation in an endophytic bacterium (Ashitha et al, 2020). Biosurfactant production is an important characteristic of Alcanivorax sp., which is an essential requirement for inhibiting the biofilm formation and biofouling growth (Qiao and Shao, 2010;Alemań-Vega et al, 2020;Mishra et al, 2020). The detection of fatty acids in the extracts along with strong antibiofilm activity in this study indicated the potential of sponge-associated Alcanivorax as a good source of antibiofilm compounds.…”
Section: Chemical Compounds From Alcanivorax Sp Extractsmentioning
confidence: 60%
“…Despite of being widely studied, with a few exceptions, the use of biosurfactants within the pharmaceutical industry is today limited. Regarding replacing biosurfactants with chemical surfactants, biosurfactants are today used in cosmetics and in food, but in other industrial applications such as bioremediation and antifouling, the research is still at laboratorial level [46,47]. However, as the research continues, that may change one day.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, in a recent work, a bacterial strain ( Bacillus niabensis , My-30) associated to the sponge Mycale ramulosa (Gulf of California) showed a clear activity in the collapsing drop test and emulsification properties with high stability for 24 h, compared to the control (Sodium Dodecyl Sulfate, SDS). Moreover, supernatants of My-30 demonstrated a promising antifouling activity, with Minimum Inhibitory Concentration (MIC) values of 1–2% ( v/v ), against Bacillus subtilis , Micrococcus sp., and Sagittula stellata [ 88 ].…”
Section: Sponge Symbionts In Cosmeceutical Fieldmentioning
confidence: 99%